Peran Aṭṭhasīanī dalam Pembinaan Sekolah Minggu Buddha di Tangerang - Keti Keti (Jurnal Ilmiah Kampus: Sati Sampajanna, 2021)
The purpose of the study was to know the role of aṭṭhasīlanī based on theresponse  of  Buddhists  in  the  construction  of  the  Sunday  Buddhist  School  inTangerang. The types of research used are measures that are used systematically to collect data in conducting research and assisting the creation of scientific work. This paper uses quantitative research methods. The subjects of this study were Buddhist Sunday School students and parents. The object of this research is the role of aṭṭhasīlanī in the construction of the Buddhist Sunday School in Tangerang City. Data collection techniques using survey methods, disseminating questionnaires to students of The Sunday School of Buddha. Data validity techniques use validity and reliability tests. Data analysis techniques use absolute norms. The data analysis in this study was with the help of Microsoft Excel. Then the results of the data processing were described to find out the role of ahasīlani in the construction of the Buddhist Sunday School in Tangerang.  Data collected from 90 respondents showed the average score reached a score of 98.43 obtained from the number of scores divided by the number of respoden. The standard deviation of 12.23 and variance of 149.57 is obtained from the calculation by excell method. From the data also obtained the highest role score of 120 and the lowest role score of 84 out of the number of item scores about as many as 30 questions. The performance score range is 36. The researchers concluded that the role of the aṭṭhasīlanī was very good and active in the construction of the Sunday Buddhist School in Tangerang. The achievement of knowledge and practice of Buddhist religious attitudes was successfully achieved by the students of The Sunday School of Buddha well